DNA barcodes of Caulerpa species (Caulerpaceae, Chlorophyta) from the Northern Philippines - Dumilag, Richard V.; Balucanag, Maria Pia Sarah B.; Dulalia, Allissa Rose T.; Alcoriza, Ver Angelo M.; Aguinaldo, Zae-Zae A.; Sayasa, Arnel R. (2019)
Species discrimination in Caulerpa ? a seaweed genus of economic importance ? can be difficult because its members are often morphologically variable, occasionally with some morphological overlap between species. One of the most common approaches to circumvent this challenge is the integration of phenotypic data with information gained from short reference DNA sequences or DNA barcodes. Previous investigations based on this approach have incorporated only a limited number of specimens of Caulerpa from the Philippines. The present study aimed to identify Caulerpa collections from the northern Philippines aided with DNA barcodes. TufA gene sequence data of recent intertidal and shallow subtidal collections confirmed the presence of seven genetically recognized Caulerpa species in the northern Philippines, namely C. chemnitzia, C. cupressoides, C. elongata, C. oligophylla, C. racemosa, C. serrulata, and C. sertularioides. Caulerpa elongata and C. oligophylla were confirmed occurring in the area for the first time. With the addition of species recorded previously but not found during the present study, this brings the total number of Caulerpa species in the region to 15 species. (Author's abstract)